Socio-Cultural Approach on Disaster Risk Management of Sirnaresmi Customary Village, West Java - Iwan Permana; Rosliana Dewi; Johan Budhiana; Iyam Mariam; Lia Novianty; Rima Novianti Utami; Waqid Sanjaya; Abdul Rahman La Ede (Research Horizon, 2021)
The Sirnaresmi indigenous people are one of the communities that still maintain their traditional culture to this day. In carrying out the rules and customs in the community, Sirnaresmi Village has its own institutional structure. There are several stakeholder institutions that support landslide risk reduction in Sirnaresmi Village. This study aims to determine the socio-cultural life and disaster risk management of the customary community in Sirnaresmi Village, West Java. The result showed that efforts to reduce the risk of landslides in Sirnaresmi Village have been carried out. However, the capacity in Sirnaresmi Village is still insufficient to reduce the risk of landslides. Some possible solutions are disaster risk reduction efforts by community organizing in disaster management through the formation of Disaster Management Community Groups (KMPB) and increasing public knowledge in reducing disaster risk together with experts from the Regional Disaster Management Agency of Sukabumi Regency. The other practical implications were also suggested such as by nurturing local traditions to help reduce disaster risk and involving local leadership roles in disaster risk reduction efforts.